2021
DOI: 10.3390/ijerph18158222
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Active Arts Engagement on Health and Well-Being of Older Adults: A Nation-Wide Participatory Study

Abstract: An emerging body of research indicates that active arts engagement can enhance older adults’ health and experienced well-being, but scientific evidence is still fragmented. There is a research gap in understanding arts engagement grounded in a multidimensional conceptualization of the value of health and well-being from older participants’ perspectives. This Dutch nation-wide study aimed to explore the broader value of arts engagement on older people’s perceived health and well-being in 18 participatory arts-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 30 publications
0
21
0
1
Order By: Relevance
“…Arts engagement can result in participants experiencing (1) positive feelings; (2) personal and artistic growth; and (3) increased meaningful social interactions. Art-based practices promote the well-being of older adults and increase their quality of life [ 34 , 35 ].…”
Section: Body Experience and Participation In Art Can Promote Success...mentioning
confidence: 99%
“…Arts engagement can result in participants experiencing (1) positive feelings; (2) personal and artistic growth; and (3) increased meaningful social interactions. Art-based practices promote the well-being of older adults and increase their quality of life [ 34 , 35 ].…”
Section: Body Experience and Participation In Art Can Promote Success...mentioning
confidence: 99%
“…Receptive arts engagement refers to activities in which the individual was an audience member (e.g., listening to music, watching a dance concert, looking at visual art). These two kinds of artistic activities have been proven to improve people's wellbeing during the epidemic ( 13 , 14 ).…”
Section: Related Workmentioning
confidence: 99%
“…Participatory arts engagement involves dancing, singing, drama performance and other activities. Research has proved that participatory arts engagement in these activities can improve the sense of experience happiness during COVID-19 ( 14 ). Arts engagement might serve as a coping mechanism in times of crisis.…”
Section: Introductionmentioning
confidence: 99%
“…There is a growing interest in the effect of arts on the well-being of older adults [ 8 , 9 , 10 ]. Art-based activities, such as music, dance, and theater, are becoming more recognized as relevant tools to enhance participants’ physical movement, communication skills, and memory through group activities [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The current studies of intergenerational art programs have shown positive effects on the well-being of older adults [ 9 , 13 ], in addition to younger generations receiving inspiration from older adults and reducing fear of growing older [ 14 ] and promoting mutual understanding between the young and old [ 9 , 11 , 15 ]. Therefore, incorporating an intergenerational approach in art-based activities has become appreciated as an opportunity for social participation for older adults [ 9 , 10 , 13 , 16 ].…”
Section: Introductionmentioning
confidence: 99%